Pengaruh Perencanaan dan Penganggaran terhadap Kinerja Perangkat Daerah pada Badan Perencanaan Pembangunan Daerah Kabupaten Kutai Timur - Ariesmawati, Yulia (Jurnal Ilmiah Administrasi Publik, 2020)
The purpose of the study is to determine planning and budgeting impact partially on as performance indicator of the regional organization in Regional Development Planning Departement of East Kutai Regency in East Kalimantan Province. This research using quantitative approach, with responden survey method, which was conducted on 58 State Civil Apparatuses (ASN) with qualification minimum hold bachelor degree as responden. Data analysis using descriptive and inferential statistics. The results describe that there ware positive and significant correlation between planning and budgeting impact in partially with performance of regional organization in Regional Development Planning Department (Bappeda) East Kutai Timur.